Cataloguing based on bibliographic axiology - Guerrini, Mauro (JLIS.it, 2010)
The article presents the work of Elaine Svenonius The Intellectual Foundation of Information Organization, translated in Italian and published by Le Lettere of Florence, within the series Pinakes, with the title Il fondamento intellettuale dell’organizzazione dell’informazione. The Intellectual Foundation of Information Organization defines the theoretical aspects of library science, its philosophical basics and principles, the purposes that must be kept in mind, abstracting from the technology used in a library. The book deals with information organization and bibliographic universe, in particular using the bibliographic entities defined in FRBR, at first. Then, it analyzes all the specific languages by which works and subjects are treated. This work, already acknowledged as a classic, organizes, synthesizes and make easily understood the whole complex of knowledge, practices and procedures developed in the last 150 years.